1998
DOI: 10.2115/fiber.54.10_538
|View full text |Cite
|
Sign up to set email alerts
|

Strain-hardening Property and Internal Deformation of Polymer Composite Melts under Uniaxial Elongation.

Abstract: Uniaxial elongational viscosity of low density polyethylene (LDPE) gave the strain-hardening property. However, talc-filled LDPE showed almost no strain-hardening property and glass-fiber-filled LDPE exhibited the strain-softening property. The cause of almost no strain-hardening property or strain-softening property was discussed from flow observation of internal deformation using visual model experiments. Silicone gums including a glass bead or a glass fiber with a black silicone gum marker were elongated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
3
9
0
Order By: Relevance
“…Finally, the samples were broken after showing necking phenomenon. This decreasing behavior of viscosity agreed with the results reported in the previous paper [4][5][6][7][8][9] and the strain-softening origin seemed to be explained by the idea that undeformed particles generate complex flows around the particles.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Finally, the samples were broken after showing necking phenomenon. This decreasing behavior of viscosity agreed with the results reported in the previous paper [4][5][6][7][8][9] and the strain-softening origin seemed to be explained by the idea that undeformed particles generate complex flows around the particles.…”
Section: Resultssupporting
confidence: 92%
“…Elongational flow behavior of ABS (AcrylonitrileButadiene-Styrene) resins was often reported. [1][2][3] In general, it is known that ABS exhibits a weaker strain-hardening in elongational flow which is similar to that of polymer composite systems [4][5][6][7][8][9] than matrix AS (Acrylonitrile-Styrene Copolymer).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Takahashi et al found that glass-fiber-filled LDPE exhibited strainsoftening properties. 24 Takahashi et al also reported that the strain-softening was observed in ABS copolymers containing hard crosslinked butadiene particles. 25 The presence of hard particles seemed to be the key factor in both these cases, which was responsible for strain-softening properties.…”
Section: Uniaxial Elongational Viscositymentioning
confidence: 95%